White lesions - oral leukoplakia, a premalignant lesion - Holmstrup, Palle (Henry Stewart Talks, 2017)
Malignant transformation of oral leukoplakia, Oral leukoplakia development to carcinoma, Oral leukoplakia follow ups, Aetiological malignant potential, Types of oral leukoplakia, Malignancy relation to candidal infections, Mycological aetiology of oral mucosal cancer, HPV as revealed by PAP, ISH, PCR or BLOT, Topographical malignant potential, Surgical treatment of oral premalignant lesions, Risk lesions, Long-term treatment of oral premalignant lesions, Surgical treatment of premalignant lesions